Ekspektasi Kinerja Pembelajaran Online di Perguruan Tinggi Jakarta - William Surjadinata (ULTIMA InfoSys, 2014)
This research calculates performance expectation of online learning system in Jakarta Undergraduate Universities. The main goal of the research is to calculate the difference of online learning system performance expectation between non experienced students and lecturers compared to the experienced students and lecturers. Data is gathered by using random sampling method, questionnaire, and analyzed in experimental research. Result of analysis shows that there is no significant difference of online learning system performance expectation between experienced and inexperienced users. It is can be concluded that online learning system still cannot be able to give a good performance expectation to users in Jakarta Undergraduate Universities. Furthermore education institution should make a better plan and evaluation to their online learning system. Index Terms - Expectation, Online, Performance, Learning